Design of Web-Based Barcore Stock Information System and FJLB Pine at PT Karya Bhakti Manunggal - Sulistiyasni Sulistiyasni; Joko Purnomo; Muhammad Hery Santoso; Endang Setyawati (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2020)
Karya Bhakti Manunggal Company is located in Purbalingga, operating since 1991 is a company selling and distributing various kinds of leisure wood products albasia and pine. Data loss occurs when users intentionally or unintentionally delete documents or overwrite documents and process data inventory into finished Microsoft Office Excel often delayed by officers so that the final inventory of finished goods produced sometimes does not match the physical stock in the warehouse.The purpose of this study was to create a Website-based wood stock application on facilitate the processing of barecore and fjlb finished goods iventory data at Karya Bhakti Manunggal Company. Stages of research include data collection, namely interviews, observation, study of literature, documentation and questionnaires. The author uses the Rapid Application Develoment (RAD) system development method which consists of 3 stages, namely requirements planning, workshop design, and implementation. Based on the test results of the product test getting a value of 83.3%, the benefit test gets a value of 80%, it can be concluded that the product test and benefit test have been successful. The conclusion of the results of this study is the Barcore and FJLB Pine Finished Stock Information System which is designed and built is able to facilitate data management of new goods, manage goods coming in and out, and speeding up the making of stock reports of Karya Bhakti Manunggal Compay.